Lead-free ceramic, preparation method thereof and capacitor
By introducing BKT and BZT ceramics into lead-free ceramics, the material composition and preparation process are optimized, and the shortcomings of existing lead-free ceramics in high power density and energy storage efficiency are solved, and efficient energy conversion and storage are achieved.
Patent Information
- Application Number
- CN202411996931.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing lead-free ceramic energy storage materials are difficult to meet the needs of new technology development in terms of power density and energy storage efficiency, especially in situations where high energy density and high power density coexist.
By optimizing the material composition, BKT ceramics and BZT ceramics are introduced, the paraelectric phase of ST ceramics is broken, the degree of ion disorder at the A crystal position is increased, the relaxation characteristics are improved, and the dual crystal disorder relaxation ferroelectric is formed by reducing the sintering temperature and introducing Zn2+, and the power density is improved.
It realizes the high power density and excellent energy storage characteristics of lead-free ceramics, improving energy conversion efficiency and energy storage performance.
Smart Images

Figure CN119797907A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic technology, and in particular to a lead-free ceramic and a preparation method thereof, and a capacitor. Background Art
[0002] With the continuous growth of global energy demand and the increasingly severe environmental problems, finding efficient and environmentally friendly energy storage and conversion technologies has become an important topic in the current scientific and technological field. In the power system, capacitors are key energy storage components, and their performance directly affects the efficiency and stability of the entire system. Therefore, the development of capacitor materials with high power density and excellent energy storage characteristics has become a research hotspot.
[0003] Traditional capacitor materials, such as polymer energy storage materials, although showing good performance in some aspects, still have a lot of room for improvement in power density and energy storage efficiency. In contrast, ceramic energy storage materials show a broader application prospect due to their high dielectric constant, low dielectric loss, good mechanical properties and temperature stability. However, most lead-free ceramic energy storage materials still cannot meet the needs of further development of new technologies in terms of power density and energy storage efficiency, especially in situations where high energy density and high power density coexist. Power density is an indicator of the maximum power that a capacitor can output per unit volume or unit weight, which is crucial to improving energy conversion efficiency and system compactness. The energy storage characteristics focus on the energy storage and release capacity of the capacitor during the charging and discharging process, which directly affects its service life and stability. Therefore, the development of a lead-free ceramic material with both high power density and excellent energy storage characteristics is of great significance to promote the development of power systems and related electronic equipment. Summary of the invention
[0004] The present application provides a lead-free ceramic and a preparation method thereof, and a capacitor, so as to improve the energy conversion efficiency and energy storage characteristics of the lead-free ceramic.
[0005] In a first aspect, the present application provides a lead-free ceramic, wherein the lead-free ceramic comprises a material having a chemical formula of xSrTiO 3 -yBi a K b TiO 3 -zBi(Zn c Ti d ) 3 Represents the main components, where x+y+z=1, a+b=1, c+d=1.
[0006] As an optional embodiment, the main component satisfies at least one of the following conditions (1) to (7):
[0007] (1) 0.78 ≤ x ≤ 0.98;
[0008] (2) 0.01≤y≤0.13;
[0009] (3) 0.01≤z≤0.09;
[0010] (4) 0.4≤a≤0.6;
[0011] (5) 0.4≤b≤0.6;
[0012] (6) 0.4≤c≤0.6;
[0013] (7)0.4≤d≤0.6.
[0014] As an optional embodiment, the main component satisfies at least one of the following conditions (8) to (14):
[0015] (8) 0.84 ≤ x ≤ 0.92;
[0016] (9) 0.05≤y≤0.09;
[0017] (10) 0.03≤z≤0.07;
[0018] (11)0.45≤a≤0.55;
[0019] (12) 0.45≤b≤0.55;
[0020] (13)0.45≤c≤0.55;
[0021] (14)0.45≤d≤0.55.
[0022] As an optional embodiment, the lead-free ceramic includes a material having a chemical formula of 0.88SrTiO 3 -0.07Bi 0.5 K 0.5 TiO 3 -0.05Bi(Zn 0.5 Ti 0.5 ) 3 Represents the main component.
[0023] As an optional implementation manner, the mass proportion of the main component in the lead-free ceramic is ≥90%.
[0024] As an optional implementation manner, the mass proportion of the main component in the lead-free ceramic is 95% to 100%.
[0025] In a second aspect, the present application provides a method for preparing the lead-free ceramic of the first aspect, the method comprising:
[0026] The raw materials are mixed and subjected to a first ball milling process to obtain a first mixed material;
[0027] Pre-sintering the first mixed material to obtain a pre-sintered powder;
[0028] The pre-sintered powder is subjected to a second ball milling process to obtain a second mixed material;
[0029] The second mixed material is subjected to a molding process to obtain a ceramic component;
[0030] The ceramic component is sintered to obtain lead-free ceramic.
[0031] As an optional implementation, the raw materials include Sr source, K source, Bi source, Ti source and Zn source.
[0032] As an optional embodiment, the sintering temperature is 1000° C. to 1300° C.; and / or
[0033] The sintering time is 1h to 3h; and / or
[0034] The heating rate of the sintering process is 3°C / min to 7°C / min.
[0035] In a third aspect, the present application provides a capacitor, wherein the material of the capacitor includes the lead-free ceramic provided in the first aspect.
[0036] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0037] The lead-free ceramic provided in the embodiment of the present application is a BKT ceramic (Bi a K b TiO 3 ) is dissolved into ST ceramics (SrTiO 3 ) so that the A crystal position is Bi 3+ , K + , Sr 2+ , the paraelectric phase in ST ceramics is broken by the introduction of BKT ceramics, Bi 3+ and Sr 2+ The composite of distorts the lattice, increases the ion disorder of the A crystal position, and improves its relaxation characteristics. At the same time, the introduction of BZT ceramics (Bi(Zn c Ti d ) 3 ), BZT ceramics are a low melting point material, which can reduce the overall sintering temperature, thereby reducing the probability of the ceramic forming a liquid phase during sintering. And the introduction of BZT ceramics can be added to the B crystal position Zn 2+ , so that it has Ti in the B crystal position 4+ 、Zn2+ , making its microscopic ordering disordered, and finally forming a twin-site disordered relaxor ferroelectric, which is beneficial to the power density of lead-free ceramics. In addition, the grains of BKT ceramics are small, and the reduction of grain size reduces the number of oxygen vacancies. These oxygen vacancies are oxidized again during the sintering process, further reducing oxygen vacancies, and fewer oxygen vacancies inhibit the growth of grains, which eventually leads to a reduction in grain size and the formation of more grain boundaries. The existence of grain boundaries leads to the formation of space charge depletion layers, which hinders the transmission of carriers, making the grain boundaries have higher resistivity. Therefore, there are more grain boundaries in ceramics with small grain sizes, but the area is smaller, and the leakage current is smaller, resulting in a higher breakdown field strength, which is beneficial to the improvement of the material's energy storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0040] Figure 1 A schematic diagram of a process for a method provided in an embodiment of the present application;
[0041] Figure 2 A unipolar hysteresis loop diagram of the lead-free ceramic provided in Example 1 of the present application at 10 Hz;
[0042] Figure 3 This is the over-damped charge and discharge diagram of the lead-free ceramic provided in Example 1 of the present application. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0045] Most lead-free ceramic energy storage materials still cannot meet the needs of further development of new technologies in terms of power density and energy storage efficiency, especially in situations where high energy density and high power density coexist.
[0046] This application intends to achieve a dual improvement in power density and energy storage characteristics through the optimization of material composition and the improvement of preparation process. By deeply studying the relationship between the microstructure, phase composition and performance of ceramic materials, lead-free ceramic materials with high power density and excellent energy storage characteristics are prepared.
[0047] The present application provides a lead-free ceramic, wherein the lead-free ceramic comprises
[0048] xSrTiO 3 -yBi a K b TiO 3 -zBi(Zn c Ti d ) 3 Represents the main components, where x+y+z=1, a+b=1, c+d=1.
[0049] The lead-free ceramic will be BKT ceramic (Bi a K b TiO 3 ) is dissolved into ST ceramics (SrTiO 3 ) so that the A crystal position is Bi 3+ , K + , Sr 2+ , the paraelectric phase in ST ceramics is broken by the introduction of BKT ceramics, Bi 3+ and Sr 2+ The composite of distorts the lattice, increases the ion disorder of the A crystal position, and improves its relaxation characteristics. At the same time, the introduction of BZT ceramics (Bi(Zn c Ti d ) 3 ), BZT ceramics are a low melting point material, which can reduce the overall sintering temperature, thereby reducing the probability of the ceramic forming a liquid phase during sintering. And the introduction of BZT ceramics can be added to the B crystal position Zn 2+ , so that it has Ti in the B crystal position 4+ 、Zn 2+, making its microscopic ordering disordered, and finally forming a twin-site disordered relaxor ferroelectric, which is beneficial to the power density of lead-free ceramics. In addition, the grains of BKT ceramics are small, and the reduction of grain size reduces the number of oxygen vacancies. These oxygen vacancies are oxidized again during the sintering process, further reducing oxygen vacancies, and fewer oxygen vacancies inhibit the growth of grains, which eventually leads to a reduction in grain size and the formation of more grain boundaries. The existence of grain boundaries leads to the formation of space charge depletion layers, which hinders the transmission of carriers, making the grain boundaries have higher resistivity. Therefore, there are more grain boundaries in ceramics with small grain sizes, but the area is smaller, and the leakage current is smaller, resulting in a higher breakdown field strength, which is beneficial to the improvement of the material's energy storage performance.
[0050] In some embodiments, 0.78≤x≤0.98, and further, 0.84≤x≤0.92. Exemplarily, the value of x can be 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, etc., and it can also be any value within the range of 0.78≤x≤0.98.
[0051] In some embodiments, 0.01≤y≤0.13, further, 0.05≤y≤0.09. Exemplarily, the value of y can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, etc., and it can also be any value within the range of 0.01≤y≤0.13.
[0052] In some embodiments, 0.01≤z≤0.09, and further, 0.03≤z≤0.07. For example, the value of z can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, etc., and can also be any value within the range of 0.01≤z≤0.09.
[0053] In some embodiments, 0.4≤a≤0.6, further, 0.45≤a≤0.55. For example, the value of a can be 0.4, 0.42, 0.45, 0.47, 0.5, 0.52, 0.55, 0.57, 0.6, etc., and it can also be any value within the range of 0.4≤a≤0.6.
[0054] In some embodiments, 0.4≤b≤0.6, further, 0.45≤b≤0.55. Exemplarily, the value of b can be 0.4, 0.42, 0.45, 0.47, 0.5, 0.52, 0.55, 0.57, 0.6, etc., and can also be any value within the range of 0.4≤b≤0.6.
[0055] In some embodiments, 0.4≤c≤0.6, further, 0.45≤c≤0.55. Exemplarily, the value of c can be 0.4, 0.42, 0.45, 0.47, 0.5, 0.52, 0.55, 0.57, 0.6, etc., and can also be any value within the range of 0.4≤c≤0.6.
[0056] In some embodiments, 0.4≤d≤0.6, further, 0.45≤d≤0.55. Exemplarily, the value of d can be 0.4, 0.42, 0.45, 0.47, 0.5, 0.52, 0.55, 0.57, 0.6, etc., and can also be any value within the range of 0.4≤d≤0.6.
[0057] In some embodiments, the lead-free ceramic comprises a material having a chemical formula of 0.88SrTiO 3 -0.07Bi 0.5 K 0.5 TiO 3 -0.05Bi(Zn 0.5 Ti 0.5 ) 3 Represents the main component.
[0058] In some embodiments, the mass proportion of the main component in the lead-free ceramic is ≥ 90%. Further, the mass proportion of the main component in the lead-free ceramic is 95% to 100%. The higher the mass proportion of the main component, the more conducive it is to give full play to its energy conversion efficiency and energy storage characteristics.
[0059] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, based on a general inventive concept, the embodiment of the present application also provides a method for preparing lead-free ceramics.
[0060] This method is used to prepare the above-mentioned lead-free ceramics. The specific content of the lead-free ceramics can refer to the above-mentioned embodiments. Since this method adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0061] In some embodiments, the method comprises:
[0062] S1. The raw materials are mixed and subjected to a first ball milling process to obtain a first mixture;
[0063] In some embodiments, the raw materials include Sr source, K source, Bi source, Ti source and Zn source. Among them, the Sr source can be specifically selected from SrCO 3 , K source is selected from K 2 CO 3 The Bi source can be selected from Bi 2 O 3 The Ti source can be specifically selected from TiO 2 , the Zn source can specifically be selected from ZnO.
[0064] In some embodiments, the first ball milling treatment includes: mixing anhydrous ethanol, the mixed raw materials, and ball milling beads in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s. The slurry after the first ball milling treatment is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120°C. After drying, the sample is passed through a 60-mesh sieve.
[0065] S2. The first mixture is pre-sintered to obtain a pre-sintered powder;
[0066] In some embodiments, the pre-sintering process involves placing the powder into a furnace at 800° C. and keeping the temperature for 3 hours, and then taking it out after cooling it to room temperature.
[0067] S3. The pre-sintered powder is subjected to a second ball milling process to obtain a second mixture;
[0068] In some embodiments, the second ball milling treatment includes ball milling the pre-sintered powder for a second time, with the same process control as the first ball milling treatment, and ball milling for 12 hours. After ball milling, the slurry is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh screen.
[0069] S4. The second mixture is subjected to a molding process to obtain a ceramic component;
[0070] In some embodiments, the molding process can be dry pressing with PVA added, and the template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0071] S5. Sintering the ceramic component to obtain lead-free ceramic.
[0072] In some embodiments, the temperature of the sintering treatment is 1000° C. to 1300° C.; the time of the sintering treatment is 1 h to 3 h; and the heating rate of the sintering treatment is 3° C. / min to 7° C. / min.
[0073] Specifically, in this embodiment, the ceramic blank with the ceramic component is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, and then cooled to room temperature and taken out. Both sides of the sample are polished, cleaned and dried to obtain lead-free ceramics.
[0074] Based on a general inventive concept, an embodiment of the present application further provides a capacitor, wherein the material of the capacitor includes the lead-free ceramic provided above.
[0075] The capacitor is realized based on the above-mentioned lead-free ceramic. The specific content of the lead-free ceramic can refer to the above-mentioned embodiment. Since the capacitor adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0076] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0077] Example 1
[0078] A lead-free ceramic, the preparation process of which includes:
[0079] (1) The raw material SrCO 3 (mass purity 99%), K 2 CO 3 (mass purity 99.98%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (mass purity 99.8%), ZnO (mass purity 99%) according to the chemical composition 0.88SrTiO 3 -0.07Bi 1 / 2 K 1 / 2 TiO 3 -0.05Bi(Zn 1 / 2 Ti 1 / 2 ) 3 After evenly mixing, put it into the ball mill.
[0080] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0081] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0082] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0083] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0084] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0085] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0086] Example 2
[0087] A lead-free ceramic, the preparation process of which includes:
[0088] (1) The raw material SrCO 3 (mass purity 99%), K 2 CO 3 (mass purity 99.98%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (mass purity 99.8%), ZnO (mass purity 99%) according to the chemical composition
[0089] 0.78SrTiO 3 -0.13Bi 1 / 2 K 1 / 2 TiO 3 -0.09Bi(Zn 1 / 2 Ti 1 / 2 ) 3 After evenly mixing, put it into the ball mill.
[0090] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0091] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0092] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0093] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0094] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0095] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0096] Example 3
[0097] A lead-free ceramic, the preparation process of which includes:
[0098] (1) The raw material SrCO 3 (mass purity 99%), K 2 CO 3 (mass purity 99.98%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (mass purity 99.8%), ZnO (mass purity 99%) according to the chemical composition
[0099] 0.98SrTiO 3 -0.01Bi 1 / 2 K 1 / 2 TiO 3 -0.01Bi(Zn 1 / 2 Ti 1 / 2 ) 3 After evenly mixing, put it into the ball mill.
[0100] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0101] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0102] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0103] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0104] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0105] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0106] Example 4
[0107] A lead-free ceramic, the preparation process of which includes:
[0108] (1) The raw material SrCO 3 (mass purity 99%), K 2 CO 3 (mass purity 99.98%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (mass purity 99.8%), ZnO (mass purity 99%) according to the chemical composition
[0109] 0.84SrTiO 3 -0.09Bi 1 / 2 K 1 / 2 TiO 3 -0.07Bi(Zn 1 / 2 Ti 1 / 2 ) 3 After evenly mixing, put it into the ball mill.
[0110] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0111] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0112] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0113] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0114] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0115] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0116] Example 5
[0117] A lead-free ceramic, the preparation process of which includes:
[0118] (1) The raw material SrCO 3 (mass purity 99%), K 2 CO 3 (mass purity 99.98%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (mass purity 99.8%), ZnO (mass purity 99%) according to the chemical composition
[0119] 0.92SrTiO 3 -0.05Bi 1 / 2 K 1 / 2 TiO 3 -0.03Bi(Zn 1 / 2 Ti 1 / 2 ) 3 After evenly mixing, put it into the ball mill.
[0120] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0121] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0122] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0123] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0124] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0125] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0126] Comparative Example 1
[0127] A lead-free ceramic, the preparation process of which includes:
[0128] (1) The raw material SrCO 3 (mass purity 99%), K 2 CO 3 (mass purity 99.98%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (Mass purity 99.8%) According to the chemical composition 0.93SrTiO 3 -0.07Bi 1 / 2 K 1 / 2 TiO 3 After evenly mixing, put it into the ball mill.
[0129] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0130] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0131] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0132] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0133] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0134] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0135] Comparative Example 2
[0136] A lead-free ceramic, the preparation process of which includes:
[0137] (1) The raw material SrCO 3 (mass purity 99%), Bi 2 O 3 (mass purity 99.9%), TiO 2 (mass purity 99.8%), ZnO (mass purity 99%) according to the chemical composition 0.95SrTiO 3 -0.05Bi(Zn 1 / 2 Ti 1 / 2 ) 3 After evenly mixing, put it into the ball mill.
[0138] (2) Anhydrous ethanol, the mixed raw materials, and ball milling beads are mixed in a certain ratio for the first ball milling treatment, that is, methanol: raw materials: ball milling beads = 1:1:1.2. The ball milling time is 24 hours, and the ball milling speed is 5 rad / s to obtain a first mixed material.
[0139] (3) The first mixed material after ball milling is placed in a rotary drying device for drying, and the dimethyl silicone oil at the bottom is heated to 120° C. After drying, the sample is passed through a 60-mesh sieve.
[0140] (4) The dried first mixed material is placed in a furnace at 800° C. and kept at this temperature for 3 hours for pre-sintering, and then cooled to room temperature and taken out to obtain a pre-sintered powder.
[0141] (5) The pre-sintered powder is subjected to a second ball milling treatment, the parameters of the second ball milling treatment are the same as the first ball milling treatment, and the ball milling is performed for 12 hours. After ball milling, the rotary drying step is repeated and the powder is re-sieved to obtain a second mixed material.
[0142] (6) PVA is added to the second mixed material for dry pressing. The template for the molding process adopts a circular ceramic blank, which is a disc with a diameter of 10 mm and a thickness of 1 mm, to obtain a ceramic component.
[0143] (7) The ceramic blank with the ceramic components is placed in a heating furnace, heated to 1150°C at a heating rate of 5°C / min, sintered and kept warm for 2 hours, then cooled to room temperature and taken out of the furnace; both sides are polished and cleaned, washed and dried to obtain lead-free ceramics.
[0144] The electrical properties of the lead-free ceramics provided in Examples 1 to 5 and Comparative Examples 1 to 2 were tested, and the tests included:
[0145] Energy storage density and energy storage efficiency test: The lead-free ceramics to be tested are polished to a thickness of 0.2 mm, and the electrodes are sprayed with gold electrodes. The size of the gold electrodes on both sides is 0.0314 cm 2 During the test, the lead-free ceramic to be tested is immersed in silicone oil. Through the PE curve obtained by the test, the maximum polarization intensity, residual polarization intensity, and coercive field size can be obtained, and then the effective energy storage density and energy storage efficiency of the material can be calculated.
[0146] Charge and discharge test: Add voltage to the two ends of the lead-free ceramic to be tested, then suddenly remove the voltage, and observe the relationship between its discharge waveform and discharge time. It is mainly in two states: overdamping and underdamping. The following formula is used to calculate based on the measurement results.
[0147]
[0148] Where I max is the peak current (A), S is the electrode area (cm 2 ), E is the applied electric field strength (kV / cm), and h is the sample thickness (mm).
[0149] The results are shown in the following table:
[0150]
[0151] It can be seen from the above table that the lead-free ceramics provided by the embodiments of the present application have good energy conversion efficiency and energy storage characteristics.
[0152] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0153] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.
[0154] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A lead-free ceramic, characterized in that: The lead-free ceramic includes a material having a chemical formula of xSrTiO3-yBi a K b TiO3-zBi(Zn c Ti d )O3 represents the main component, wherein x+y+z=1, a+b=1, c+d=1.
2. The lead-free ceramic according to claim 1, characterized in that: The main component satisfies at least one of the following conditions (1) to (7): (1)0.78≤x≤0.98; (2)0.01≤y≤0.13; (3)0.01≤z≤0.09; (4)0.4≤a≤0.6; (5)0.4≤b≤0.6; (6)0.4≤c≤0.6; (7)0.4≤d≤0.6。 3. The lead-free ceramic according to claim 2, characterized in that: The main component satisfies at least one of the following conditions (8) to (14): (8)0.84≤x≤0.92; (9)0.05≤y≤0.09; (10)0.03≤z≤0.07; (11)0.45≤a≤0.55; (12)0.45≤b≤0.55; (13)0.45≤c≤0.55; (14)0.45≤d≤0.55。 4. The lead-free ceramic according to claim 3, characterized in that: The lead-free ceramic comprises a chemical formula of 0.88SrTiO3-0.07Bi 0.5 K 0.5 TiO3-0.05Bi(Zn 0.5 Ti 0.5 )O3 represents the main component.
5. The lead-free ceramic according to any one of claims 1 to 4, characterized in that The mass proportion of the main component in the lead-free ceramic is ≥90%.
6. The lead-free ceramic according to claim 5, characterized in that: The mass percentage of the main component in the lead-free ceramic is 95% to 100%.
7. A method for preparing the lead-free ceramic according to any one of claims 1 to 6, characterized in that: The method comprises: The raw materials are mixed and subjected to a first ball milling process to obtain a first mixed material; Pre-sintering the first mixed material to obtain a pre-sintered powder; The pre-sintered powder is subjected to a second ball milling process to obtain a second mixed material; The second mixed material is subjected to a molding process to obtain a ceramic component; The ceramic component is sintered to obtain lead-free ceramic.
8. The method for preparing lead-free ceramics according to claim 7, characterized in that: The raw materials include Sr source, K source, Bi source, Ti source and Zn source.
9. The method for preparing lead-free ceramics according to any one of claims 7 to 8, characterized in that: The sintering temperature is 1000°C to 1300°C; and / or The sintering time is 1h to 3h; and / or The heating rate of the sintering process is 3°C / min to 7°C / min.
10. A capacitor, characterized in that: The material of the capacitor includes the lead-free ceramic according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-temperature stable lead-free capacitor ceramic dielectric material and preparation method thereof
CN103265283A
Highly-oriented lead-free piezoelectric textured ceramic material and preparation method and application thereof
CN104628379A
Bismuth-based lead-free high energy storage density ceramic material and preparation method thereof
CN109354492A
Preparation method of barium strontium titanate-based solid solution system negative temperature coefficient thermal sensitive ceramic
CN118255584A
Ceramics and method for manufacturing the same
JP2012193049A